Glassine paper and production process thereof
By steam blasting the wood and bamboo, combined with lithium aluminum silicate, modified cellulose and adhesives, the problem of insufficient degradation performance of traditional gracin paper is solved, and higher tightness, strength and oil resistance are achieved, while improving biodegradation performance.
Patent Information
- Application Number
- CN202411650014.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-19
AI Technical Summary
Traditional grazing paper has shortcomings in its degradation performance and is difficult to meet increasingly stringent environmental protection requirements.
By steam blasting the crushed wood and bamboo, the lignin and cellulose structure is destroyed, and the steam blasting material is combined with lithium aluminum silicate, modified cellulose, and adhesive, and the net is copied, pressed, dried and applied to make gracin paper.
Improves the biodegradable properties of grazing paper while enhancing its tightness, strength and oil resistance.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of papermaking, and in particular to glassine paper and a production process thereof. Background Art
[0002] Glassine paper is favored by the market for its high gloss, smoothness, moisture-proof and waterproof properties. However, glassine paper produced using traditional production processes still has shortcomings in terms of degradation performance and is difficult to meet increasingly stringent environmental protection requirements.
[0003] Accordingly, the art needs a new technical solution to solve the above problems. Summary of the invention
[0004] In order to solve at least one of the above problems in the prior art, that is, to solve the problem of how to improve the degradation performance of glassine paper, the present application provides a production process of glassine paper, comprising:
[0005] a) subjecting the crushed wood and bamboo to steam explosion treatment at 0.5-0.8 MPa for 5-10 min, at 1-1.5 MPa for 1-2 h, and at 2-2.4 MPa for 10-20 min, and obtaining blasting materials after pressure relief;
[0006] b) adding lithium aluminum silicate, modified cellulose and an adhesive to the blasting material obtained in step a), grinding and obtaining a mixed slurry;
[0007] c) subjecting the mixed slurry to papermaking, pressing and drying in sequence to obtain base paper;
[0008] d) sizing the base paper on its surface, drying it, and calendering it to obtain glassine paper.
[0009] In the preferred technical solution of the above production process, step a) specifically includes:
[0010] The crushed wood and bamboo are placed in a steam explosion device, and the pressure is increased to 0.5-0.8 MPa at a temperature of 120-200° C. and a pressure increase rate of 0.3-0.5 MPa / min and maintained for 5-10 minutes;
[0011] Raise the pressure to 1-1.5MPa at a rate of 0.2-0.4MPa / min and maintain for 1-2h;
[0012] Raise the pressure to 2-2.4 MPa at a rate of 0.1-0.3 MPa / min and maintain for 10-20 min;
[0013] The pressure is released at a rate of 50-100 MPa / min to obtain blasting materials.
[0014] In the preferred technical scheme of the above production process, in step a), the particle size ranges of the crushed wood include 1μm-10μm, 10μm-50μm, 50μm-500μm and 500μm-1mm, wherein the mass ratio of the wood in these four ranges is (2-4): (1-2): (5-10): (1-3).
[0015] In the preferred technical scheme of the above production process, in step a), the particle size ranges of the crushed bamboo material include 10μm-50μm, 50μm-500μm, 500μm-1mm and 1-10mm, wherein the mass ratio of the wood in these four ranges is (1-2): (2-4): (3-5): (0.5-1).
[0016] In the preferred technical scheme of the above production process, the method for preparing the modified cellulose comprises:
[0017] The cellulose, carbonamide and alkaline solution are mixed, and then dodecyltrimethylammonium chloride and starch are added in a water bath at 50-70°C, stirred for 10-20 hours, neutralized with an acidic solution, washed, filtered and dried to obtain modified cellulose.
[0018] In the preferred technical scheme of the above production process, the mass ratio of the cellulose, the carbon amide, the alkaline solution, dodecyltrimethylammonium chloride and starch is (1-3): (0.5-1): (50-100): (0.05-0.1): (0.5-1), and the alkali concentration in the alkaline solution is 5-10 vol%.
[0019] In the preferred technical scheme of the above production process, the mass ratio of the blasting material, lithium aluminum silicate, modified cellulose and adhesive is (6-12): (0.1-0.3): (1-2): (1-2).
[0020] In the preferred technical solution of the above production process, the mass concentration of the mixed slurry is 3-5%.
[0021] In the preferred technical scheme of the above production process, the adhesive includes one or more of polyvinyl alcohol, guar gum, gul gum, xanthan gum, and gum arabic.
[0022] The present application also discloses a glassine paper, which is produced by the production process described in any of the above preferred technical solutions.
[0023] The beneficial effects of the present invention are:
[0024] It can be understood by those skilled in the art that the production process of glassine paper of the present application can not only soften the wood and bamboo, but also destroy the lignin and hemicellulose structure in the wood and bamboo by steam explosion treatment, thereby helping to improve the biodegradability of glassine paper. In addition, by using the explosion material obtained after steam explosion treatment with lithium aluminum silicate, modified cellulose, and adhesive as materials for making glassine paper, it is not only conducive to improving the degradation performance of glassine paper, but also can improve the compactness, high strength, and good oil resistance of glassine paper. DETAILED DESCRIPTION
[0025] The present invention provides a production process of glassine paper, comprising the following steps:
[0026] a) subjecting the crushed wood and bamboo to steam explosion treatment at 0.5-0.8 MPa for 5-10 min, at 1-1.5 MPa for 1-2 h, and at 2-2.4 MPa for 10-20 min, and obtaining blasting materials after pressure relief;
[0027] b) adding lithium aluminum silicate, modified cellulose and an adhesive to the blasting material obtained in step a), grinding and obtaining a mixed slurry;
[0028] c) subjecting the mixed slurry to papermaking, pressing and drying in sequence to obtain base paper;
[0029] d) Surface sizing is performed on the base paper, and after drying, calendering is performed to obtain glassine paper.
[0030] The present application not only softens the wood and bamboo by subjecting them to steam explosion, but also destroys the lignin and cellulose structures in the wood and bamboo, thereby helping to improve the biodegradability of glassine paper. In addition, by using the explosion material obtained after steam explosion with lithium aluminum silicate, modified cellulose, and adhesive as materials for making glassine paper, it is not only conducive to improving the degradation performance of glassine paper, but also can improve the tightness, high strength, and good oil resistance of glassine paper.
[0031] In step a), the crushed wood and bamboo are subjected to steam explosion treatment at 0.5-0.8 MPa for 5-10 min, at 1-1.5 MPa for 1-2 h, and at 2-2.4 MPa for 10-20 min, and then the pressure is released to obtain the exploded material. The steam explosion treatment of wood and bamboo can destroy the lignin and hemicellulose structure in the wood and bamboo, thereby helping to improve the biodegradability of glassine paper.
[0032] In an exemplary embodiment, the particle size range of the wood after crushing in the present invention includes 1μm-10μm, 10μm-50μm, 50μm-500μm and 500μm-1mm, wherein the mass ratio of the wood in these four ranges is (2-4): (1-2): (5-10): (1-3). By subjecting the above-mentioned wood to steam explosion treatment, the inter-fiber bonding force of glassine paper can be increased, so that the strength of glassine paper is improved. The particle size range of the bamboo after crushing includes 10μm-50μm, 50μm-500μm, 500μm-1mm and 1-10mm, wherein the mass ratio of the wood in these four ranges is (1-2): (2-4): (3-5): (0.5-1). By subjecting the above-mentioned bamboo to steam explosion treatment, the inter-fiber bonding force of glassine paper can also be improved. In addition, steam explosion treatment using bamboo and wood in the above particle size range can not only increase the compactness of glassine paper, but also help to enhance the strength of glassine paper. It should be noted that the mass ratio of wood to bamboo is (1-3): (1-3).
[0033] In an exemplary embodiment, step a) specifically includes: placing the crushed wood and bamboo in a steam explosion device, raising the pressure to 0.5-0.8MPa at a pressure increase rate of 0.3-0.5MPa / min at a temperature of 120-200°C and maintaining it for 5-10min; raising the pressure to 1-1.5MPa at a pressure increase rate of 0.2-0.4MPa / min and maintaining it for 1-2h; raising the pressure to 2-2.4MPa at a pressure increase rate of 0.1-0.3MPa / min and maintaining it for 10-20min; releasing the pressure at a pressure reduction rate of 50-100MPa / min to obtain a blasting material. By gradually increasing the pressure of bamboo and wood and maintaining different pressure stages in the above manner, the cell walls of the wood and bamboo are effectively destroyed, making the fibers soft and easy to disperse. This not only improves the uniformity of the fibers in the pulp, so that the flatness and strength of the glassine paper are improved, but also significantly improves the degradation performance. It should be noted that the pressure is increased by introducing steam into the steam explosion equipment.
[0034] In step b), lithium aluminum silicate, modified cellulose and adhesive are added to the blasting material obtained in step a), and the mixture is ground to obtain a mixed slurry. By adding lithium aluminum silicate, modified cellulose and adhesive to the blasting material, it is not only beneficial to improve the degradation performance of glassine paper, but also to improve the tightness, high strength and good oil resistance of glassine paper.
[0035] It should be noted that the use of lithium aluminum silicate can effectively improve the dimensional stability of paper at different temperatures and reduce paper deformation caused by temperature changes, wherein the lithium aluminum silicate includes a small particle size of 0.1-1 μm, a fine particle size of 1-5 μm and a large particle size of 5-20 μm in a mass ratio of (3-5): (1-2): (0.5-1). By using different particle sizes for grading, the roughness of glassine paper can also be improved, so that the connection strength between the base paper and the sizing agent can be improved in the subsequent sizing process.
[0036] In an exemplary embodiment, the method for preparing modified cellulose includes: mixing cellulose, carbonamide and an alkaline solution, then adding dodecyl trimethyl ammonium chloride and starch under a water bath condition of 50-70°C, stirring for 10-20 hours, neutralizing with an acidic solution, washing, filtering and drying to obtain modified cellulose. By modifying cellulose, the oleophobic properties of base paper can be improved, and it is also beneficial to paper forming and paper quality. Among them, the present application is not limited to cellulose, which can be one or both of hydroxyethyl cellulose and hydroxypropyl cellulose. The mass ratio of cellulose, the carbonamide, the alkaline solution, dodecyl trimethyl ammonium chloride and starch is (1-3): (0.5-1): (50-100): (0.05-0.1): (0.5-1), and the alkali concentration in the alkaline solution is 5-10vol%. The alkaline solution can be a KOH solution or a NaOH solution.
[0037] In an exemplary embodiment, the mass ratio of the blasting material, lithium aluminum silicate, modified cellulose, and adhesive is (6-12):(0.1-0.3):(1-2):(1-2).
[0038] In an exemplary embodiment, the mass concentration of the mixed slurry is 3-5%. In addition, the adhesive includes one or more of polyvinyl alcohol, guar gum, gul gum, xanthan gum, and gum arabic.
[0039] In step c), the mixed slurry is sequentially subjected to wire papermaking, pressing, and drying to obtain base paper;
[0040] Among them, the web making, pressing and drying are all conventional techniques in the art and will not be elaborated here.
[0041] In step d), the sizing agent used in the sizing process is paraffin emulsion, carboxymethyl cellulose or styrene-maleic anhydride copolymer. By applying the above sizing agent on the base paper, the oil resistance of glassine paper can be improved. In addition, the surface sizing coating amount is 10-30g / m 2 By adopting the above coating amount, the flatness of glassine paper can be improved.
[0042] The present invention is illustrated with reference to the following examples.
[0043] Example 1
[0044] The production process of glassine paper includes the following steps:
[0045] a) crushing wood and bamboo in a mass ratio of 1:1 respectively, wherein the sizes of the wood after crushing include 1μm-10μm, 10μm-50μm, 50μm-500μm and 500μm-1mm, and the mass ratio is 3:1.2:8:1.5; the sizes of the bamboo after crushing include 10μm-50μm, 50μm-500μm, 500μm-1mm and 1-10mm, and the mass ratio is 1.5:3:4:0.8;
[0046] The crushed wood and bamboo are mixed and put into the steam explosion equipment, heated to 150°C, and the pressure is increased to 0.7MPa at a pressure increase rate of 0.4MPa / min and maintained for 8min; the pressure is increased to 1.2MPa at a pressure increase rate of 0.3MPa / min and maintained for 1.5h; the pressure is increased to 2.2MPa at a pressure increase rate of 0.2MPa / min and maintained for 15min; the pressure is released at a pressure reduction rate of 80MPa / min to obtain the blasting material;
[0047] b) adding lithium aluminum silicate, modified cellulose and adhesive to the blasting material obtained in step a), wherein the mass ratio of the blasting material to lithium aluminum silicate, modified cellulose and adhesive is 10:0.2:1.5:1.5, adding water and grinding to obtain a mixed slurry with a mass concentration of 4%;
[0048] The lithium aluminum silicate comprises a small particle size of 0.1-1 μm, a microparticle size of 1-5 μm and a large particle size of 5-20 μm in a mass ratio of 4:1.5:0.8; the preparation method of the modified cellulose comprises: mixing hydroxyethyl cellulose, carbon amide and a NaOH solution with a concentration of 7 vol%, then adding dodecyl trimethyl ammonium chloride and starch in a water bath at 60°C, stirring for 15 hours, neutralizing the pH value to 6 with an HCl solution, washing, filtering and drying to obtain the modified cellulose; the mass ratio of hydroxyethyl cellulose, carbon amide, NaOH solution, dodecyl trimethyl ammonium chloride and starch is 2:0.75:80:0.07:0.8; the adhesive comprises polyvinyl alcohol and xanthan gum in a mass ratio of 2:1;
[0049] c) subjecting the mixed slurry to papermaking, pressing and drying in sequence to obtain base paper;
[0050] d) Surface sizing the base paper, drying and calendering to obtain glassine paper; wherein the sizing agent is carboxymethyl cellulose with a solid content of 30%, and the surface sizing coating amount is 20g / m 2 .
[0051] Example 2
[0052] The production process of glassine paper includes the following steps:
[0053] a) crushing wood and bamboo in a mass ratio of 2:1 respectively, wherein the sizes of the wood after crushing include 1μm-10μm, 10μm-50μm, 50μm-500μm and 500μm-1mm, and the mass ratio is 2.5:1.5:7:2; the sizes of the bamboo after crushing include 10μm-50μm, 50μm-500μm, 500μm-1mm and 1-10mm, and the mass ratio is 1.8:3.5:3.5:0.7;
[0054] The crushed wood and bamboo are mixed and put into the steam explosion equipment, heated to 180°C, and the pressure is increased to 0.6MPa at a pressure increase rate of 0.35MPa / min and maintained for 8min; the pressure is increased to 1.3MPa at a pressure increase rate of 0.25MPa / min and maintained for 1.2h; the pressure is increased to 2.3MPa at a pressure increase rate of 0.15MPa / min and maintained for 18min; the pressure is released at a pressure reduction rate of 90MPa / min to obtain the blasting material;
[0055] b) adding lithium aluminum silicate, modified cellulose and adhesive to the blasting material obtained in step a), wherein the mass ratio of the blasting material to lithium aluminum silicate, modified cellulose and adhesive is 8:0.15:1.3:1.4, adding water and grinding to obtain a mixed slurry with a mass concentration of 3.5%;
[0056] The lithium aluminum silicate comprises a small particle size of 0.1-1 μm, a microparticle size of 1-5 μm and a large particle size of 5-20 μm in a mass ratio of 4.5:1.8:0.7; the preparation method of the modified cellulose comprises: mixing hydroxypropyl cellulose, carbon amide and a KOH solution with a concentration of 6 vol%, then adding dodecyl trimethyl ammonium chloride and starch under a water bath condition of 55°C, stirring for 18 hours, neutralizing the pH value to 6 with an HCl solution, washing, filtering and drying to obtain the modified cellulose; the mass ratio of hydroxypropyl cellulose, carbon amide, KOH solution, dodecyl trimethyl ammonium chloride and starch is 1.5:0.9:80:0.06:0.65; the adhesive comprises polyvinyl alcohol;
[0057] c) subjecting the mixed slurry to papermaking, pressing and drying in sequence to obtain base paper;
[0058] d) applying size to the base paper surface, drying it, and calendering it to obtain glassine paper;
[0059] The sizing agent is a paraffin emulsion with a solid content of 40wt%, and the surface sizing coating amount is 15g / m 2 .
[0060] Example 3
[0061] The production process of glassine paper includes the following steps:
[0062] a) crushing wood and bamboo in a mass ratio of 1:2 respectively, wherein the sizes of the wood after crushing include 1μm-10μm, 10μm-50μm, 50μm-500μm and 500μm-1mm, and the mass ratio is 3.5:1.8:6:2.5; the sizes of the bamboo after crushing include 10μm-50μm, 50μm-500μm, 500μm-1mm and 1-10mm, and the mass ratio is 1.2:2.5:4.5:0.6;
[0063] The crushed wood and bamboo are mixed and put into the steam explosion equipment, heated to 160°C, and the pressure is increased to 0.75MPa at a pressure increase rate of 0.45MPa / min and maintained for 7min; the pressure is increased to 1.4MPa at a pressure increase rate of 0.35MPa / min and maintained for 1.5h; the pressure is increased to 2.1MPa at a pressure increase rate of 0.25MPa / min and maintained for 18min; the pressure is released at a pressure reduction rate of 80MPa / min to obtain the blasting material;
[0064] b) adding lithium aluminum silicate, modified cellulose and adhesive to the blasting material obtained in step a), wherein the mass ratio of the blasting material to lithium aluminum silicate, modified cellulose and adhesive is 10:0.25:1.8:1.5, adding water and grinding to obtain a mixed slurry with a mass concentration of 4.5%;
[0065] The lithium aluminum silicate comprises a small particle size of 0.1-1 μm, a microparticle size of 1-5 μm and a large particle size of 5-20 μm in a mass ratio of 4.5:1.8:0.75; the preparation method of the modified cellulose comprises: mixing hydroxyethyl cellulose, carbonamide and a NaOH solution with a concentration of 9 vol%, then adding dodecyl trimethyl ammonium chloride and starch under a water bath condition of 65°C, stirring for 15 hours, neutralizing the pH value to 6 with an HCl solution, washing, filtering and drying to obtain the modified cellulose; the mass ratio of hydroxyethyl cellulose, carbonamide, NaOH solution, dodecyl trimethyl ammonium chloride and starch is 2.5:0.6:60:0.06:0.9; the adhesive comprises polyvinyl alcohol, guar gum and guar gum in a mass ratio of 2:0.5:0.5;
[0066] c) subjecting the mixed slurry to papermaking, pressing and drying in sequence to obtain base paper;
[0067] d) applying size to the base paper surface, drying it, and calendering it to obtain glassine paper;
[0068] The sizing agent is a styrene-maleic anhydride copolymer with a solid content of 60wt%, and the surface sizing coating amount is 25g / m 2 .
[0069] Example 4
[0070] The production process of glassine paper includes the following steps:
[0071] a) crushing wood and bamboo in a mass ratio of 1:3 respectively, the sizes of the wood after crushing include 1μm-10μm, 10μm-50μm, 50μm-500μm and 500μm-1mm, and the mass ratio is 2:1:5:1; the sizes of the bamboo after crushing include 10μm-50μm, 50μm-500μm, 500μm-1mm and 1-10mm, and the mass ratio is 1:2:3:0.5;
[0072] The crushed wood and bamboo are mixed and put into the steam explosion equipment, heated to 120°C, and the pressure is increased to 0.5MPa at a pressure increase rate of 0.3MPa / min and maintained for 10min; the pressure is increased to 1MPa at a pressure increase rate of 0.2MPa / min and maintained for 2h; the pressure is increased to 2MPa at a pressure increase rate of 0.1MPa / min and maintained for 20min; the pressure is released at a pressure reduction rate of 100MPa / min to obtain the blasting material;
[0073] b) adding lithium aluminum silicate, modified cellulose and an adhesive to the blasting material obtained in step a), wherein the mass ratio of the blasting material to the lithium aluminum silicate, the modified cellulose and the adhesive is 6:0.1:1:1, adding water and grinding to obtain a mixed slurry with a mass concentration of 3%;
[0074] The lithium aluminum silicate includes small particles of 0.1-1 μm, microparticles of 1-5 μm and large particles of 5-20 μm in a mass ratio of 3:1:0.5; the preparation method of the modified cellulose includes: mixing hydroxypropyl cellulose, carbonamide and a NaOH solution with a concentration of 5 vol%, then adding dodecyl trimethyl ammonium chloride and starch under a water bath condition of 50°C, stirring for 10 hours, neutralizing the pH value to 6 with an HCl solution, washing, filtering and drying to obtain the modified cellulose; the mass ratio of hydroxypropyl cellulose, carbonamide, NaOH solution, dodecyl trimethyl ammonium chloride and starch is 1:0.5:50:0.05:0.5; the adhesive includes guar gum and xanthan gum in a mass ratio of 1:1;
[0075] c) subjecting the mixed slurry to papermaking, pressing and drying in sequence to obtain base paper;
[0076] d) applying size to the base paper surface, drying it, and calendering it to obtain glassine paper;
[0077] The sizing agent is carboxymethyl cellulose with a solid content of 55wt%, and the surface sizing coating amount is 10g / m 2 .
[0078] Example 5
[0079] The production process of glassine paper includes the following steps:
[0080] a) crushing wood and bamboo in a mass ratio of 3:1 respectively, wherein the sizes of the wood after crushing include 1μm-10μm, 10μm-50μm, 50μm-500μm and 500μm-1mm, and the mass ratio is 4:2:10:3; the sizes of the bamboo after crushing include 10μm-50μm, 50μm-500μm, 500μm-1mm and 1-10mm, and the mass ratio is 2:4:5:1;
[0081] The crushed wood and bamboo are mixed and put into the steam explosion equipment, heated to 200°C, and then the pressure is increased to 0.8MPa at a pressure increase rate of 0.5MPa / min and maintained for 5min; the pressure is increased to 1.5MPa at a pressure increase rate of 0.4MPa / min and maintained for 1h; the pressure is increased to 2.4MPa at a pressure increase rate of 0.3MPa / min and maintained for 10min; the pressure is released at a pressure reduction rate of 50MPa / min to obtain the blasting material;
[0082] b) adding lithium aluminum silicate, modified cellulose and adhesive to the blasting material obtained in step a), wherein the mass ratio of the blasting material to lithium aluminum silicate, modified cellulose and adhesive is 12:0.3:2:2, adding water and grinding to obtain a mixed slurry with a mass concentration of 5%;
[0083] The lithium aluminum silicate includes a small particle size of 0.1-1 μm, a microparticle size of 1-5 μm and a large particle size of 5-20 μm in a mass ratio of 5:2:1; the preparation method of the modified cellulose includes: mixing hydroxyethyl cellulose, carbonamide and a KOH solution with a concentration of 10 vol%, then adding dodecyl trimethyl ammonium chloride and starch under a water bath condition of 70°C, stirring for 20 hours, neutralizing the pH value to 6 with an HCl solution, washing, filtering and drying to obtain the modified cellulose; the mass ratio of hydroxyethyl cellulose, carbonamide, KOH solution, dodecyl trimethyl ammonium chloride and starch is 3:1:100:0.1:1; the adhesive includes gum arabic;
[0084] c) subjecting the mixed slurry to papermaking, pressing and drying in sequence to obtain base paper;
[0085] d) applying size to the base paper surface, drying it, and calendering it to obtain glassine paper;
[0086] The sizing agent is a paraffin emulsion with a solid content of 40wt%, and the surface sizing coating amount is 30g / m 2 .
[0087] Comparative Example 1
[0088] The only difference from Example 1 is step a), and the specific differences are as follows:
[0089] The wood and bamboo with a mass ratio of 1:1 are crushed respectively. The size of the wood after crushing is 500μm-1mm, and the size of the bamboo after crushing includes 10μm-50μm, 50μm-500μm, 500μm-1mm and 1-10mm. The mass ratio is 1.5:3:4:0.8.
[0090] Comparative Example 2
[0091] The only difference from Example 1 is step a), and the specific differences are as follows:
[0092] Step a) is specifically:
[0093] The wood and bamboo with a mass ratio of 1:1 were crushed respectively. The sizes of the wood after crushing included 1μm-10μm, 10μm-50μm, 50μm-500μm and 500μm-1mm, and the mass ratio was 3:
[0094] 1.2:8:1.5; The size of the crushed bamboo is 1mm-10mm.
[0095] Comparative Example 3
[0096] The only difference from Example 1 is step a), and the specific differences are as follows:
[0097] The wood and bamboo with a mass ratio of 1:1 are crushed respectively. The sizes of the wood after crushing include 10μm-50μm, 50μm-500μm and 500μm-1mm, and the mass ratio is 4.2:8:1.5; the sizes of the bamboo after crushing include 10μm-50μm, 50μm-500μm, 500μm-1mm and 1-10mm, and the mass ratio is 1.5:3:4:0.8.
[0098] Comparative Example 4
[0099] The only difference from Example 1 is step a), and the specific differences are as follows:
[0100] The wood and bamboo with a mass ratio of 1:1 were crushed respectively. The sizes of the wood after crushing included 1μm-10μm, 10μm-50μm, 50μm-500μm and 500μm-1mm, and the mass ratio was 3:
[0101] 1.2:8:1.5; the sizes of the crushed bamboo include 50μm-500μm, 500μm-1mm and 1-10mm, with a mass ratio of 4.5:4:0.8.
[0102] Comparative Example 5
[0103] The only difference from Example 1 is step a), and the specific differences are as follows:
[0104] The wood and bamboo with a mass ratio of 1:1 are crushed respectively. The sizes of the wood after crushing include 50-500μm and 500μm-1mm, and the mass ratio after crushing is 4.2:2.3; the sizes of the bamboo after crushing include 10μm-50μm and 500μm-1mm, and the mass ratio is 4.5:4.8.
[0105] Comparative Example 6
[0106] The only difference from Example 2 is step a), and the specific differences are as follows:
[0107] The crushed wood and bamboo are mixed and put into a steam explosion device. After heating to 180°C, the pressure is increased to 2.3MPa at a pressure increase rate of 0.35MPa / min and maintained for 98min; the pressure is released at a pressure reduction rate of 90MPa / min to obtain a blasting material.
[0108] Comparative Example 7
[0109] The only difference from Example 2 is step a), and the specific differences are as follows:
[0110] The crushed wood and bamboo are mixed and put into the steam explosion equipment. After heating to 180°C, the pressure is increased to 0.6MPa at a pressure increase rate of 0.35MPa / min and maintained for 8min; the pressure is increased to 2.3MPa at a pressure increase rate of 0.25MPa / min and maintained for 90min; the pressure is released at a pressure reduction rate of 90MPa / min to obtain the blasting material.
[0111] Comparative Example 8
[0112] The only difference from Example 2 is step a), and the specific differences are as follows:
[0113] The crushed wood and bamboo are mixed and put into the steam explosion equipment, heated to 180°C, and the pressure is increased to 0.6MPa at a pressure increase rate of 0.15MPa / min and maintained for 8min; the pressure is increased to 1.3MPa at a pressure increase rate of 0.35MPa / min and maintained for 1.2h; the pressure is increased to 2.3MPa at a pressure increase rate of 0.25MPa / min and maintained for 18min; the pressure is released at a pressure reduction rate of 90MPa / min to obtain the blasting material;
[0114] Comparative Example 9
[0115] The only difference from Example 2 is step a), and the specific differences are as follows:
[0116] The crushed wood and bamboo are mixed and put into the steam explosion equipment. After heating to 180°C, the pressure is increased to 0.6MPa at a pressure increase rate of 0.35MPa / min and maintained for 8min; the pressure is increased to 1.3MPa at a pressure increase rate of 0.25MPa / min and maintained for 1.2h; the pressure is increased to 2.3MPa at a pressure increase rate of 0.15MPa / min and maintained for 18min; the pressure is released at a pressure reduction rate of 30MPa / min to obtain blasting materials.
[0117] Comparative Example 10
[0118] The only difference from Example 2 is step a), and the specific differences are as follows:
[0119] The crushed wood and bamboo are mixed and put into the steam explosion equipment. After heating to 180°C, the pressure is increased to 0.6MPa at a pressure increase rate of 0.35MPa / min and maintained for 8min; the pressure is increased to 1.3MPa at a pressure increase rate of 0.25MPa / min and maintained for 1.2h; the pressure is increased to 2.3MPa at a pressure increase rate of 0.15MPa / min and maintained for 18min; the pressure is released at a pressure reduction rate of 150MPa / min to obtain blasting materials.
[0120] Comparative Example 11
[0121] The only difference from Example 3 is step b), and the specific differences are as follows:
[0122] Add lithium aluminum silicate, hydroxypropyl cellulose and adhesive to the blasting material obtained in step a), wherein the mass ratio of the blasting material to lithium aluminum silicate, hydroxypropyl cellulose and adhesive is 8:0.15:1.3:1.4, add water and grind to obtain a mixed slurry with a mass concentration of 3.5%.
[0123] Comparative Example 12
[0124] The only difference from Example 3 is step b), and the specific differences are as follows:
[0125] Modified cellulose and adhesive are added to the blasting material obtained in step a), wherein the mass ratio of blasting material to lithium aluminum silicate, modified cellulose and adhesive is 8:1.3:1.4, and water is added and then ground to obtain a mixed slurry with a mass concentration of 3.5%.
[0126] Comparative Example 13
[0127] The only difference from Example 4 is step b), and the specific differences are as follows:
[0128] The lithium aluminum silicate includes a small particle size of 0.1-1 μm and a large particle size of 5-20 μm in a mass ratio of 3:0.5.
[0129] Comparative Example 14
[0130] The only difference from Example 4 is step a), and the specific differences are as follows:
[0131] Lithium aluminum silicate has a small particle size of 0.1-1 μm.
[0132] Comparative Example 15
[0133] The only difference from Example 4 is step b), and the specific differences are as follows:
[0134] The particle size of lithium aluminum silicate is 1-5 μm.
[0135] Comparative Example 16
[0136] The only difference from Example 4 is step b), and the specific differences are as follows:
[0137] Lithium aluminum silicate has a large particle size of 5-20 μm.
[0138] The glassine papers prepared in Examples 1-5 and Comparative Examples 1-16 were tested for tightness, roughness, oleophobicity, tensile strength, and tear strength according to GB / T29282-2024, and the degree of glassine disintegration was tested according to GB / T39951-2021. The results are shown in Table 1.
[0139] Table 1 Performance parameters of Examples 1-5 and Comparative Examples 1-16
[0140]
[0141]
[0142] It can be seen from the experimental data in Table 1 that the glassine paper prepared in Examples 1-5 is superior to the glassine paper prepared in Comparative Documents 1-16 in terms of tightness, roughness, oleophobicity, tensile strength, and tear strength, and has good degradation performance.
[0143] Those skilled in the art will appreciate that, although some embodiments described herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the claims of the present application, any one of the claimed embodiments may be used in any combination.
[0144] It should be noted that although the detailed steps of the method of the present application are described in detail above, without departing from the basic principles of the present application, technical personnel in this field can combine, split and change the order of the above steps. The modified technical solution does not change the basic concept of the present application and therefore falls within the scope of protection of the present application.
[0145] So far, the technical solutions of the present application have been described in conjunction with the preferred embodiments, but it is easy for those skilled in the art to understand that the protection scope of the present application is obviously not limited to these specific embodiments. Without departing from the principles of the present application, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present application.
Claims
1. A production process for glassine paper, characterized in that: include: a) subjecting the crushed wood and bamboo to steam explosion treatment at 0.5-0.8 MPa for 5-10 min, at 1-1.5 MPa for 1-2 h, and at 2-2.4 MPa for 10-20 min, and obtaining blasting materials after pressure relief; b) adding lithium aluminum silicate, modified cellulose and an adhesive to the blasting material obtained in step a), grinding and obtaining a mixed slurry; c) subjecting the mixed slurry to papermaking, pressing and drying in sequence to obtain base paper; d) sizing the base paper on its surface, drying it, and calendering it to obtain glassine paper.
2. The production process according to claim 1, characterized in that: Step a) specifically includes: The crushed wood and bamboo are placed in a steam explosion device, and the pressure is increased to 0.5-0.8 MPa at a temperature of 120-200° C. and a pressure increase rate of 0.3-0.5 MPa / min and maintained for 5-10 minutes; Raise the pressure to 1-1.5MPa at a rate of 0.2-0.4MPa / min and maintain for 1-2h; Raise the pressure to 2-2.4 MPa at a rate of 0.1-0.3 MPa / min and maintain for 10-20 min; The pressure is released at a rate of 50-100 MPa / min to obtain blasting materials.
3. The production process according to claim 1, characterized in that: In step a), the particle size ranges of the crushed wood include 1 μm-10 μm, 10 μm-50 μm, 50 μm-500 μm and 500 μm-1 mm, wherein the mass ratio of the wood in these four ranges is (2-4): (1-2): (5-10): (1-3).
4. The production process according to claim 1, characterized in that: In step a), the particle size ranges of the crushed bamboo include 10 μm-50 μm, 50 μm-500 μm, 500 μm-1 mm and 1-10 mm, wherein the mass ratios of the wood in these four ranges are (1-2): (2-4): (3-5): (0.5-1).
5. The production process according to claim 1, characterized in that: The preparation method of the modified cellulose comprises: The cellulose, carbonamide and alkaline solution are mixed, and then dodecyltrimethylammonium chloride and starch are added in a water bath at 50-70°C, stirred for 10-20 hours, neutralized with an acidic solution, washed, filtered and dried to obtain modified cellulose.
6. The production process according to claim 5, characterized in that: The mass ratio of the cellulose, the carbonamide, the alkaline solution, dodecyltrimethylammonium chloride and starch is (1-3): (0.5-1): (50-100): (0.05-0.1): (0.5-1), and the alkali concentration in the alkaline solution is 5-10 vol%.
7. The production process according to claim 1, characterized in that: The mass ratio of the blasting material, lithium aluminum silicate, modified cellulose and adhesive is (6-12):(0.1-0.3):(1-2):(1-2).
8. The production process according to claim 1, characterized in that: The mass concentration of the mixed slurry is 3-5%.
9. The production process according to claim 1, characterized in that: The adhesive includes one or more of polyvinyl alcohol, guar gum, gul gum, xanthan gum and gum arabic.
10. A glassine paper, characterized in that: The glassine paper is produced by the production process described in any one of claims 1 to 9.
Citation Information
Patent Citations
Production process for corrugated paperboard
CN105507073A
Making technology for degradable Glasin release paper
CN108049249A
High-yield pulp release paper production process
CN112709088A
Kraft linerboard made of bamboo wood and method for preparing kraft linerboard by utilizing bamboo wood
CN115478448A
Preparation method of low-basis-weight high-strength glassine paper
CN118686005A